2008
DOI: 10.1152/ajpendo.90411.2008
|View full text |Cite
|
Sign up to set email alerts
|

Disassociation between the effects of amino acids and insulin on signaling, ubiquitin ligases, and protein turnover in human muscle

Abstract: We determined the effects of intravenous infusion of amino acids (AA) at serum insulin of 5, 30, 72, and 167 mU/l on anabolic signaling, expression of ubiquitin-proteasome components, and protein turnover in muscles of healthy young men. Tripling AA availability at 5 mU/l insulin doubled incorporation of [1-13C]leucine [i.e., muscle protein synthesis (MPS), P < 0.01] without affecting the rate of leg protein breakdown (LPB; appearance of d5-phenylalanine). While keeping AA availability constant, increasing ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
386
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(440 citation statements)
references
References 36 publications
28
386
3
4
Order By: Relevance
“…The authors hypothesized a minimal role for the ubiquitin ligases in actual proteolysis but rather changes in ubiquitin ligase expression may be due to an increased demand to remodel muscle after eccentric exercise and higher demand for energy with concentric compared to eccentric exercise. Their assertions are supported, in part by others, where changes in UPS-related gene expression appeared unrelated and did not concur with changes in 26S proteasome activity or kinetic measures of muscle protein degradation (49,69,75).…”
Section: Exercise and Nutritional Modulation Of Skeletal Muscle Protementioning
confidence: 86%
“…The authors hypothesized a minimal role for the ubiquitin ligases in actual proteolysis but rather changes in ubiquitin ligase expression may be due to an increased demand to remodel muscle after eccentric exercise and higher demand for energy with concentric compared to eccentric exercise. Their assertions are supported, in part by others, where changes in UPS-related gene expression appeared unrelated and did not concur with changes in 26S proteasome activity or kinetic measures of muscle protein degradation (49,69,75).…”
Section: Exercise and Nutritional Modulation Of Skeletal Muscle Protementioning
confidence: 86%
“…Cell based work has shown that this amino acid sensing system is incredibly sensitive with an ~7% increase in intracellular leucine leading to 50% maximal activation of mTORC1 [97]. Furthermore, only a fraction of maximal mTORC1 activity (~30%) is required to fully saturate muscle protein synthesis [98,99]. The amino acid sensing by mTORC1 also seems to be driven not by extracellular, but instead by intracellular amino acid concentrations [100].…”
Section: The Molecular Regulation Of Resistance Training Adaptation mentioning
confidence: 99%
“…As we mentioned earlier, carbohydrate driven increases in insulin may increase mTORC1 activity. However, when insulin is infused to supra-physiological levels mTORC1 is potently activated without a concomitant increase in muscle protein synthesis [99]. So while the data are clear that mTORC1 is required for load-induced growth [89], resistance exercise [91] and feeding [90], it is still very unclear if manipulating mTORC1 above what occurs physiologically will lead to enhanced muscle growth.…”
Section: The Molecular Regulation Of Resistance Training Adaptation mentioning
confidence: 99%
“…This may seem paradoxical because elevated levels of branched chain amino acids are usually associated with poor health and cardiovascular disease. One explanation might be the increased endothelial proliferation and accumulation of immune cells resulting in a higher diffusion of these metabolites into the circulation, but may also indirectly point to increased breakdown in the leg muscles [36,37].…”
Section: And 4)mentioning
confidence: 99%